2018
DOI: 10.1007/s41982-017-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Entity and Antiquity of the Aurignacian at Willendorf (Austria): Implications for Modern Human Emergence in Europe

Abstract: The time of the Aurignacian's first appearance in the archeological record lies at the heart of debates on the emergence of European anatomically modern humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…Previous age estimates of the KC4 maxilla (Higham et al, 2011) suggested there could have been a~5000-year period between~45 and 40 ka in which H. sapiens and Neanderthals may have overlapped in Europe. Suggestions of a comparably early modern presence at Cavallo (Italy) and Willendorf (Austria) have also been challenged recently (Zilhão et al, 2015;Teyssandier and Zilhão, 2018), although there is another recent claim of a similarly early modern human presence recorded at Bajondillo Cave in southern Spain (Cortés-Sánchez et al, 2019). Homo sapiens and Neanderthal interactions may have had considerably greater longevity in the Near East from~120 ka (Hovers, 2006) and probably even older (Hershkovitz et al, 2018).…”
Section: Archaeological Perspectives On Hominin Behaviourmentioning
confidence: 99%
“…Previous age estimates of the KC4 maxilla (Higham et al, 2011) suggested there could have been a~5000-year period between~45 and 40 ka in which H. sapiens and Neanderthals may have overlapped in Europe. Suggestions of a comparably early modern presence at Cavallo (Italy) and Willendorf (Austria) have also been challenged recently (Zilhão et al, 2015;Teyssandier and Zilhão, 2018), although there is another recent claim of a similarly early modern human presence recorded at Bajondillo Cave in southern Spain (Cortés-Sánchez et al, 2019). Homo sapiens and Neanderthal interactions may have had considerably greater longevity in the Near East from~120 ka (Hovers, 2006) and probably even older (Hershkovitz et al, 2018).…”
Section: Archaeological Perspectives On Hominin Behaviourmentioning
confidence: 99%
“…Due to the overall paucity of diagnostic skeletal remains, the timing and nature of anatomically modern human (AMH) dispersal into Europe and the demise of Neanderthals is reconstructed largely via archaeological proxies, with different archaeological assemblage types taken to represent biologically distinct populations (e.g., Higham et al, 2014;Hublin, 2015;Kadowaki et al, 2015;Roussel et al, 2016;Teyssandier and Zilhão, 2018). The biological transition is broadly coeval with the appearance of Early Upper Paleolithic (EUP: ~37-30 ka BP 1 ; ~42-34 ka cal BP) assemblages, while preceding European Late Middle Paleolithic (LMP) assemblages are generally accepted as being made by Neanderthals.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest assemblages generally agreed to be of AMH authorship are Proto-and Early Aurignacian (Zilhão, 2013;Higham et al, 2014;Nigst et al, 2014;Benazzi et al, 2015;Hublin, 2015;Kadowaki et al, 2015;Roussel et al, 2016;Teyssandier and Zilhão, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations